Psychometric Properties of an Instrument That Measures Adolescent Attitudes Towards Electronic Waste Management - Pascuas-Rengifo, Yois (2021)
The use and consumption of mobile devices are increasing thanks to easy access to this type of technology, which inherently increases the generation of electronic waste. The objective of this study is to determine the psychometric properties of an instrument that measures adolescent attitudes towards the management of electronic waste. A validation of content and construct supported by the application of exploratory and confirmatory factorial analysis was performed. The findings show that this scale could be applied in high school student populations and could be input for various works of research.